CLDN18-ARHGAP26 function in gastric cancer and be a new therapeutic target by ABCG2 and ABCB1 pathway - LI,Jing (2022)
Abstract Gastric cancer is one the most common human malignancies, with an increased incidence year by year. The underlying mechanisms of Claudin 18 (CLDN18) was involvement in patients with gastric cancer remain poorly understood. We therefore investigated the function of CLDN18 in patients with gastric cancer. Blood samples were collected from gastric cancer patients. CLDN18 and CLDN18 expression were measured using Microarray and qPCR. MTT assay, Transwell assay cells, LDH activity and Caspase-3/9 activity and Flow cytometry were used to measure the effects of ARHGAP26 and CLDN18 on cell growth in gastric cancer. We firstly found that CLDN18 expression were increased in patients with gastric cancer. Then, up-regulation of CLDN18 promoted cell growth in gastric cancer. Down-regulation of CLDN18 induced apoptosis in gastric cancer. Cancer-promoting genetic of CLDN18 is compromised by CLDN18-ARHGAP26 in gastric cancer cell. Down-regulation of ARHGAP26 rescues the effects of CLDN18-mediated tumor promotion effects on gastric cancer cell. CLDN18-ARHGAP26 mediated tumor suppressive effects on gastric cancer cells by ABCG2 and ABCB1 pathway. These results provide evidence that serum CLDN18-ARHGAP26 as a biomarker for tumor promoting genetic in gastric cancer via ABCG2 and ABCB1 pathway.